Determination of corrosion state of reinforced concrete structures by the parameters of color change in video image - A. A. Kuznetsov; A. V. Ponomarev; A. Yu. Kuzmenko; G. V. Volchanin (Омский научный вестник)
The article shows one of the factors influencing the formation of corrosion of hollow reinforced concrete structures — leakage currents in insulators. The development of corrosion depends on the amount of electricity that has passed through the reinforced concrete. A method for controlling the corrosion state by changing the color parameters on the video image of the reinforced concrete surface is proposed. A full-scale experiment is carried out on samples simulating various degrees of corrosion, as well as on a sample with an unknown level of corrosion. The images are obtained using an industrial endoscope.